3D Chromosome Modelling with Hi-C data - Koh, Qi Cheng (Nanyang Technological University, 2020)
3-Dimensional Chromosome Modeling has been a extensively researched topic due to the link between its structural configuration and its many functions such as the regulation of gene expression and more. Many articles have explored the different ways to use data from chromosome conformation capturing data to model the chromosomes. Some articles use probabilistic methods by analysing interaction frequencies directly while some use non-stochastic methods where they convert these interaction frequencies to distances to reconstruct the 3-D structures. Different papers have varying success in modeling chromosomes, however, this article aims to provide readers with a non-stochastic method to model chromosomes using Hi-C data. The task to do so is made out of two components mainly the conversion from interaction frequencies to corresponding distances and finding the nearest distance matrix to the actual structures.